The God of Philosophy An Introduction to Philosophy of Religion. - Jackson, Roy, 1962- (Hoboken : Taylor and Francis, 2014)
For centuries philosophers have argued about the existence and nature of God. Do we need God to explain the origins of the universe? Can there be morality without a divine source of goodness? How can God exist when there is so much evil and suffering in the world? All these questions and many more are brought to life with clarity and style in The God of Philosophy. The arguments for and against God''s existence are weighed up, along with discussion of the meaning of religious language, the concept of God and the possibility of life after death. This new edition brings the debate right up to da.
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; Introduction; 1 The concept of God; 2 The cosmological argument; 3 The teleological argument; 4 The ontological argument; 5 The moral argument; 6 The argument from religious experience; 7 Miracles; 8 Faith and reason; 9 Religious language; 10 The problem of evil and the free-will defence; 11 Life after death; 12 The 'origins' of God and the new atheism ; Index
Description based upon print version of record.
Keywords: Religion -- Philosophy; RELIGION / Philosophy; Electronic books